2019
DOI: 10.3164/jcbn.18-27
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high-affinity liposomal astaxanthin on up-regulation of age-related markers induced by oxidative stress in human corneal epithelial cells

Abstract: Decreases in tear volume, unstable tear films and excessive tear evaporation are known to cause desiccation and hyperosmolar stress. These, in turn, induce oxidative stress that is thought to cause dry eye, which is also considered to be age-related disease. We hypothesized that oxidative stress induces up-regulation of age-related markers, and that the antioxidant astaxanthin prepared as a liposomal formulation may be a candidate for the treatment of dry eye. Herein, we examined age-related markers in an in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Liposomal formulations comprising only EPC had a mostly neutral charge, and the zeta potential for liposomal formulations composed of EPC and DOTAP showed a slight positive charge (<10 mV), which is consistent with our previous report (Table 2). (23) The actual concentration of Asx encapsulated in E/Asx-lipo and E/D/Asx-lipo was nearly equal to theoretical values at 98.6% and 101.9% for E/Asx-lipo and E/D/ Asx-lipo, respectively ( Table 2).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Liposomal formulations comprising only EPC had a mostly neutral charge, and the zeta potential for liposomal formulations composed of EPC and DOTAP showed a slight positive charge (<10 mV), which is consistent with our previous report (Table 2). (23) The actual concentration of Asx encapsulated in E/Asx-lipo and E/D/Asx-lipo was nearly equal to theoretical values at 98.6% and 101.9% for E/Asx-lipo and E/D/ Asx-lipo, respectively ( Table 2).…”
Section: Resultsmentioning
confidence: 79%
“…(22) In our previous report, the liposomal formulation of Asx could suppress these phenomena in the in vitro DED model using HCECs. (23) We also demonstrated that liposomes comprising both neutral and cationic lipids that bore a slight positive charge exerted superior antioxidative effects compared to liposomes consisting of only neutral lipids. The positive surface charge is predicted to increase affinity of the liposomes for cell membranes, and thus high affinity, positively-charged liposomes should be advantageous for corneal treatments involving eye drops that typically exhibit low bioavailability due to the drainage system associated with tear flow.…”
mentioning
confidence: 64%
See 3 more Smart Citations